2017
DOI: 10.1097/md.0000000000007363
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tranexamic acid plus drain-clamping to reduce blood loss in total knee arthroplasty

Abstract: Background:Perioperative blood loss is still an unsolved problem in total knee arthroplasty (TKA). The efficacy of the preoperative use of tranexamic acid (TXA) plus drain-clamping to reduce blood loss in TKA has been debated. This meta-analysis aimed to illustrate the efficacy of TXA plus drain-clamping to reduce blood loss in patients who underwent a TKA.Methods:In February 2017, a systematic computer-based search was conducted in PubMed, EMBASE, Web of Science, the Cochrane Database of Systematic Reviews, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(36 reference statements)
1
2
0
Order By: Relevance
“…As in the previous study, [ 36 , 37 ] our meta-analysis findings showed that compared to the single strategies, the combined application of both drain-clamping and TXA administration was associated with significant reductions in total blood loss, blood loss in drainage, hemoglobin decreases, and transfusion requirements. Zhang et al [ 36 ] found that compared to TXA alone, drain-clamping alone, or control treatment, TXA plus drain-clamping achieved a maximal hemostasis effect in patients undergoing primary TKA. Furthermore, the results reported by Liao et al [ 37 ] were similar.…”
Section: Discussionsupporting
confidence: 79%
“…As in the previous study, [ 36 , 37 ] our meta-analysis findings showed that compared to the single strategies, the combined application of both drain-clamping and TXA administration was associated with significant reductions in total blood loss, blood loss in drainage, hemoglobin decreases, and transfusion requirements. Zhang et al [ 36 ] found that compared to TXA alone, drain-clamping alone, or control treatment, TXA plus drain-clamping achieved a maximal hemostasis effect in patients undergoing primary TKA. Furthermore, the results reported by Liao et al [ 37 ] were similar.…”
Section: Discussionsupporting
confidence: 79%
“…Protocols for temporary clamping time remain controversial. Previous studies 7 16 23) showed that maintaining clamping for 3 hours was more effective in reducing blood loss than no clamping or longer clamping. Jeon et al 16) reported that the drained blood volume in 3-hour clamping or 4-hour clamping was significantly less than that in conventional negative drainage.…”
Section: Discussionmentioning
confidence: 97%
“… 5) However, the combination method is more effective in lowering the volume of closed suction drainage. 5 6 7 8 9 10) …”
mentioning
confidence: 99%